Bring Up the Culture of Discipline and Behavior at The Age of Preschool Kids - Gavharoy Isroiljon kizi; Muminova Saida (Zien Journals, 2022)
This article describes the practical work being done in Uzbekistan in the field of preschool education and the specifics of teaching English from an early age, analyzed foreign experience on the formation of a culture of communication in children from an early age.
Keywords: psychology; linguistic; effective; acquisition